COMPARATIVE STUDY ON PLANNING LEGISLATION AND URBAN GOVERNANCE BETWEEN MALAYSIA AND TÜRKIYE - Rabe, Noor Suzilawati; Rushdi, Izzul Haziq; Shukri, Arif Mustaqim (Journal of Architecture, Planning and Construction Management, 2023)
This paper discusses the comparison of the planning legislation and governance between Malaysia and Türkiye. Reviews from various literature indicate that Malaysia’s development planning is primarily governed by the Town and Country Planning Act 1976, while for Türkiye, its planning systems of countries have evolved in two different ways: regulatory and discretionary planning systems. The organizational structures in Malaysia involve federal and local planning authorities, while Türkiye’s planning is overseen by the Ministry of Environment and Urbanization and its various directorates and agencies. The study has found that the decision-making processes in both countries follow a top-down approach, but recent reforms in Türkiye emphasize public participation. Implementation mechanisms involve local planning authorities in Malaysia and various directorates and agencies in Türkiye. Based on the data analysis from applied document review and content analysis, this study concluded that there are significant similarities and differences. Both countries have comprehensive planning laws but with variations in implementation and public participation.